PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENDEKATAN METODE PEMBELAJARAN PROBLEM SOLVING - Putra, Maha (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
The purpose of this research is to examine the effect of problem solving learning methods on students' critical thinking abilities. The method used is quasi-experimental with a non-equivalent group design. This research was conducted in class VIII with two classes, one experimental class and one control class, each of which used the problem solving method and the lecture method. The results of the research show that there are differences in students' critical thinking abilities using problem solving and lecture methods in improving students' critical thinking abilities. The implication is that students' critical thinking skills can be improved through the application of problem-solving learning methods.